UPFC Subsynchronous Oscillation Suppression Strategy Based on Linear Active Disturbance Rejection Control - LIU Yiqi, HUANG Xu, WANG Tianhao, ZHENG Junyuan (Dianli jianshe)
Large-scale doubly-fed wind farms connected through series-compensated transmission lines are prone to subsynchronous oscillations （SSO）， which can cause wind turbines to disconnect from the grid， posing a serious threat to the safe and stable operation of the power system. This paper proposes a control method that utilizes a unified power flow controller （UPFC） with additional damping control to mitigate SSO. The approach involves the design of a decoupled linear active disturbance rejection controller （LADRC） that uses a linear state observer to estimate the subsynchronous disturbances in the system in real time. In addition， a delay-compensation mechanism was introduced to eliminate communication delays during signal transmission. Based on the improved LADRC， an additional damping controller for the UPFC was designed to enable the UPFC to exhibit positive damping characteristics in the system， thereby suppressing SSO and enhancing the robustness and resistance of the system to disturbances. Finally， a simulation model of a doubly-fed wind farm connected to the grid through a series-compensated transmission line was developed using the MATLAB/Simulink software. The simulation results demonstrate that the proposed method effectively mitigates SSO under various conditions， including different levels of series compensation， wind speeds， and numbers of connected wind turbines. This can serve as a reference for studying similar problems of long-distance grid connections in double-fed wind farms in China.